High Expression of Complement Components in the Kidneys of Type 2 Diabetic Rats With Diabetic Nephropathy - Huang, Yinqiong; Xu, Jinting; Wu, Xiaohong; Chen, Xiaoyu; Bai, Xuefeng; Zhuang, Yong; Fang, Jingwen; Lin, Xiahong (Frontiers in Endocrinology, 2019)
Background: Diabetic nephropathy (DN) is the leading cause of end-stage failure of the kidneys; however, its pathogenesis remains unknown. This study assessed the expression of complement components in the kidneys of rats with type 2 DN to investigate their role in DN. Methods: A rat model of type 2 DN was induced by a high-fat diet combined with low-dose streptozotocin. Blood glucose, fasting insulin levels, insulin resistance index, and 24-h urinary albumin excretion (UAE) were measured. Renal tissue morphological features were observed by hematoxylin-eosin staining and periodic acid–Schiff staining; the mesangial index, arteriosclerosis index, and tube area percentage were calculated. Immunohistochemistry and western blot were used to measure the expression of complement components in the kidneys. Results: The arteriosclerosis index, mesangial index, and tube area percentage in the DN group were significantly higher than those in the control and DM groups, but these parameters did not significantly differ between the control and DM groups. The expression of the complement components C1q, mannose-binding lectin (MBL), mannan-binding lectin-associated serine protease (MASP)-2, B factor, C3, and C5b-9 in the DN group was significantly higher than that in the control and DM groups but did not significantly differ between the control and DM groups. Most of the complement components were mainly expressed at the renal tubular site. Correlation analysis showed that 24-h UAE were positively correlated with C1q, MBL, MASP-2, B factor, and C5b-9 expression. MI was positively correlated with MBL, B factor, C3, and C5b-9 expression. AI was positively correlated with C1q, MBL, MASP-2, and B factor expression. Conclusion: Complement components including C1q, MBL, MASP-2, B factor, C3, and C5b-9, were highly expressed in the kidneys of type 2 diabetic rats with DN. Most of the complement components were mainly expressed in the renal tubules. High expression of complement components was found to be associated with the progress of DN. Our study suggests that complement system activation is a progressive factor in type 2 diabetic nephropathy. Inhibition of pathological complement activation may be a promising therapeutic strategy for DN.